KEDUDUKAN HUKUM KREDITUR YANG TIDAK TERVERIFIKASI DALAM UNDANG-UNDANG KEPAILITAN - Rado Fridsel Leonardus; Novitasari (Fakultas Hukum Universitas Kristen Indonesia, 2020)
implementation of settlement in the bankruptcy process is not uncommon there are creditors with or unintentionally not exercising their right to collect at the time The debtor is declared bankrupt by the Commercial Court, the creditor is the holder the original document (certificate) belonging to the Bankrupt Debtor, to which the document was submitted by the bankrupt debtor when borrowing funds or capital to creditors through an oral agreement, while the certificate is under the control of the creditor is part of the Bankruptcy Assets and creditors do not register receivables with Curator for the debtor's bankrupt debt. Regarding this issue, what kind of mechanism which can be used in bankruptcy against these creditors as well as against actions of creditors who with or unintentionally fail to register their receivables. Law No. 37 of 2004 concerning Bankruptcy and PKPU did not mention explicitly regarding other creditors who own or control good objects in the form of documents and valuables which also have receivables from The debtor is bankrupt but the provisions of Article 61 of Law no. 37 of 2004 about Bankruptcy and PKPU stated that